Pengembangan Ensiklopedia Tumbuhan Langka di Hutan Agrowisata Taman Eden 100 Tobasa Berbasis Literasi Sains pada Mata Kuliah Taksonomi Tumbuhan - Kartika Kartika; Ashar Hasairin; Tri Harsono (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2025)
This study aimed to develop and examine the feasibility and effectiveness of a Rare Plant Encyclopedia of the Taman Eden 100 Tobasa Agrotourism Forest based on scientific literacy as teaching material for the Plant Taxonomy course. The research method employed was research and development using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included material experts, learning experts, design experts, the management of Taman Eden 100, lecturers, and Biology Education students. Research instruments consisted of validation sheets, response questionnaires, and pretest–posttest assessments. The results indicated that the developed encyclopedia achieved a very high level of feasibility based on expert evaluations. Lecturer and student responses to the use of the encyclopedia were also categorized as very good. The effectiveness test results showed an improvement in students’ scientific literacy after using the encyclopedia. In conclusion, the developed encyclopedia is feasible and sufficiently effective as teaching material and supports the enhancement of students’ scientific literacy as well as their awareness of rare plant conservation. Keywords: Encyclopedia, Scientific Literacy, Taman Eden, Rare Plants